THE DIVERSE AESTHETIC VALUES AND THEIR RELATIONSHIP TO THE LEVEL OF PERFORMANCE IN MOTOR EXPRESSION WITHIN GYMNASTIC EXERCISES (Proximus Journal of Sports Science and Physical Education, 2025)
This study aims to measure the level of motor expression among a sample of individuals practicing gymnastic exercises, using indicators that incorporate the aesthetic dimension alongside technical competence. It also seeks to identify the correlational relationship between the degree of aesthetic value appreciation and the level of motor performance, to determine the influence of aesthetics on enhancing expressive movement. The researcher adopted the descriptive survey method, which is a research approach used to examine phenomena and problems in their current environment. The research population was deliberately selected from third-year female students in the Department of Physical Education and Sports Sciences at Al-Nisour University. Specifically, fourth-year students specializing in motor expression were chosen to study their performance level and the aesthetic values evident in their movements. A random sample from this population was selected to ensure representative results, focusing on students with advanced skills and high mastery levels to guarantee the accuracy and reliability of the findings